AIAA Scitech 2020 Forum 2020
DOI: 10.2514/6.2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity to synthetic jet actuation in boundary layer flows

Abstract: The flow field generated by the interaction between a zero-net-mass-flux (synthetic) jet and a boundary layer crossflow is studied in the present work. The investigation consists in Direct Numerical Simulations (DNS) of the resulting unsteady field, for various boundary layer Reynolds numbers Re δ * 0 and jet reduced frequencies F + . In particular, the actuation frequency is chosen in order to match the unstable (or less stable) frequency of the incoming crossflow. The analysis is focused on the near-field be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Indeed, several works have demonstrated that the control of shear flows is strongly dependent both on the jet-to-crossflow momentum ratio and the ratio between the actuation frequency and a characteristic flow pulsation. Such a finding is well recognized in literature for both attached [30] and separated [31] turbulent flows.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, several works have demonstrated that the control of shear flows is strongly dependent both on the jet-to-crossflow momentum ratio and the ratio between the actuation frequency and a characteristic flow pulsation. Such a finding is well recognized in literature for both attached [30] and separated [31] turbulent flows.…”
Section: Discussionsupporting
confidence: 73%